KINETIC STUDIES ON BIODEGRADATION OF LIPIDS FROM OLIVE OIL MILL WASTEWATERS WITH FREE AND IMMOBILIZED Bacillus sp. CELLS - Anca-Irina Galaction; Dan Caşcaval; Roxana Rotaru; Anca Marcela Lupasteanu; Marius Turnea (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The studies on the biodegradation of lipids from olive oil mill wastewater with free and immobilized Bacillus sp. cells indicated that the maximum specific rate of the process is reached at pH = 8. The use of immobilized cells allows to increasing the number of biodegradation process cycles, but reduces the rate of the process. In this case, the process rate depends on the biocatalysts size and cells concentration inside them. Thus, at bacterial cells concentration of 9 g d.w./100 mL biocatalyst, the apparent specific rate varied from 4.65 to 1.46×10-2 h-1 by increasing the biocatalyst particles diameter from 3 to 4.2 mm.The cumulated influences of the particles size and cells concentration have been included in a mathematical model for the apparent specific rate of lipids biodegradation. The model offers a good concordance with the experimental data, the average deviation being of +/- 7.38%.